Avaliação do vigor de sementes de rúcula pelo teste de lixiviação de potássio - Alves, Charline Zaratin; de Sá, Marco Eustáquio [UNESP] (FapUNIFESP (SciELO), 2010)
The objective of this study was to evaluate methodologies for the potassium leaching test and to verify its sensitivity for identifying different levels of vigor of arugula seed lots. Five seed lots each of Rucula Cultivada and Rucula Gigante were used. Standard germination, first count of germination, seedling emergence and variations of the potassium leaching test (50 or 100 seeds imbibed in 50 mL or 75 mL in water; at 25 °C and 30 °C; for 0.5 h, 1 h, 1.5 h, 2 h, 2.5 h, 3, 4 and 5 hours) were done. It was observed that the period seeds need to be soaked can be reduced to 2 hours and the water volume can be reduced to 50 mL. The utilization of 50 seeds showed a smaller variation coefficient and the best temperature was 30 °C. It can be concluded that the potassium leaching test for arugula seeds can be run using 50 seeds in 50 mL of water for 2 hours at 30 °C.
Potassium leachate in arugula seeds evaluation of arugula seed vigor by the potassium leaching test
Keywords: Eruca sativa; Physiological potential; Seeds